Matematika Berbasis Alam: Menumbuhkan Rasa Ingin Tahu dan Cinta Lingkungan - Januardi, Ega; Cholily, Yus Mochamad; Syaifuddin, Mohammad (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Purpose: This study aims to address the perception of mathematics as an abstract and tedious subject by examining the effectiveness of nature-based learning in fostering cognitive curiosity and environmental stewardship. Design/methodology/approach: A qualitative case study was conducted at SDN Bunga Bangsa, Bekasi (July-August 2025), involving 2 teachers and 10 fifth-grade students. Data were gathered through participant observation, semi-structured interviews, and documentation focusing on measurement, natural element calculation, and geometry. Findings: Results indicate that direct exploration of symmetry patterns and natural object measurement significantly enhances intrinsic curiosity. The approach effectively bridges abstract concepts with concrete reality while instilling sustainability ethics using stones, twigs, and leaves as media. Students demonstrated active engagement and sustained learning motivation. Practical implications: Educators can adopt this model as a practical guide for designing adaptive contextual curricula independent of formal classroom settings. Originality/value: This research offers a holistic pedagogical model integrating numerical intelligence with ecological character education, filling a literature gap regarding the psychological mechanisms of fostering environmental love in primary mathematics education. Purpose: Penelitian ini bertujuan mengatasi persepsi matematika sebagai subjek abstrak dan membosankan dengan menguji efektivitas pembelajaran berbasis alam dalam menumbuhkan rasa ingin tahu kognitif serta karakter cinta lingkungan siswa. Design/methodology/approach: Menggunakan desain studi kasus kualitatif di SDN Bunga Bangsa, Bekasi (Juli-Agustus 2025). Subjek meliputi 2 guru dan 10 siswa kelas V. Data dikumpulkan melalui observasi partisipatif, wawancara semi-terstruktur, dan dokumentasi terhadap materi pengukuran, perhitungan elemen alam, dan geometri. Findings: Hasil menunjukkan bahwa eksplorasi langsung terhadap pola simetri dan pengukuran objek alami secara signifikan meningkatkan rasa ingin tahu intrinsik. Pembelajaran ini efektif menjembatani konsep abstrak dengan realitas konkret, sekaligus menanamkan etika keberlanjutan melalui penggunaan media batu, ranting, dan daun. Siswa menunjukkan keterlibatan aktif dan motivasi belajar yang berkelanjutan. Practical implications: Guru dapat mengadopsi model ini sebagai panduan praktis untuk merancang kurikulum kontekstual yang adaptif tanpa bergantung pada ruang kelas formal. Originality/value: Studi ini menawarkan model pedagogis holistik yang mengintegrasikan kecerdasan numerik dengan pendidikan karakter ekologis, mengisi kesenjangan literatur mengenai mekanisme psikologis penumbuhan environmental love dalam pendidikan matematika dasar.